Propiedades termodinámicas de sistemas acuosos en la escala nanoscópica - Pérez Sirkin, Yamila Anahí (2018)
Thermodynamic properties of aqueous systems in nanoscopic scaleIn the present thesis, the thermodynamical properties of aqueous systems in the nanos-cale regime were investigated. In particular, the following phenomena were analyzed: i)the vapor pressure of water-ions systems, from the macroscopic scale to aggregates ofonly a few particles. ii) The nucleation of bubbles on nanoelectrodes. iii) The effect ofconfinement on the water dissociation constant.The GCS (Grand Canonical Screening) methodology, which has been developed in ourgroup before this thesis, allows us to obtain the vapor pressure of systems that havea liquid-vapor interface. In the present thesis, this methodology has been modified inorder to study the vapor pressure of systems without an interface, with the purpose ofapplying it to more complex systems, like fuel cells. The effect of electrolytes on thevapor pressure of water has been studied from both the experimental and theoreticalpoints of view in the case of bulk systems, however the resolution of the experiments fornanoaggregate does not allow a description on the microscopic scale, and is the cause ofone of the greatest uncertainties in atmospheric predictions. In this context, we studythe ability of different models, both atomistic and coarse-grained, to predict the vaporpressure of systems of just a few molecules.The nucleation of nanobubbles on nanoscopic electrodes has been frequently studiedin recent decades, not only for its relevance from a chemical-physics standpoint, whichleaves many open questions regarding the nucleation mechanism and the stability, butalso because of its importance in the design and optimization of electrocatalytic tech-nologies. In this thesis, this phenomenon has been studied through molecular dynamicssimulations with coarse-grained models in collaboration with an experimental group atThe University of Utah.Different authors have speculated on how confinement can affect the autodissociation ofwater, but this question has not yet been answered through experiments, and has beenscarcely addressed from simulations. Recent studies suggest an increase of the dissocia-tion constant in bidimiensional nanometric pores. In the present thesis, this effect hasbeen studied under a more extreme confinement, in particular in a (6,6) carbon nano-tube, where the opposite effect was observed.To study these problems, this thesis has used different classical, quantum, and QM-MMsimulation schemes, including the following open source software: LAMMPS, MCCCS-Towhee and Quantum Espresso. It has often been necessary to implement new featureswithin these programs, as well as different tools for data analysis .